Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 434: 119



Work Step by Step

$\sqrt[4] (a^{12}b^{4}c^{20})=\sqrt[4] (a^{12}\times b^{4}\times c^{20})=\sqrt[4] (a^{12})\times \sqrt[4] (b^{4})\times \sqrt[4] (c^{20})=a^{3}bc^{5}$ $\sqrt[4] (a^{12})=a^{3}$, because $(a^{3})^{4}=a^{3\times4}=a^{12}$ $\sqrt[4] (b^{4})=b$, because $(b)^{4}=b^{4}$ $\sqrt[4] (c^{20})=c^{5}$, because $(c^{5})^{4}=c^{5\times4}=c^{20}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.